Սուրբ Աստուածածնի մշտակուսութեան գաղափարը հայրախոսական ժառանգութեան մէջ. ընդհանուր ակնարկ - Կարապետեան, Գէորգ Սրկ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В данной статье рассматривается богословское обоснование и развитие догмата о вечном девстве Пресвятой Девы Марии (Aeiparthenos) в контексте ран- нехристианской и армянской патристической традиции. Автор доказывает, что это учение — о том, что Мария осталась Девой до, во время и после рождения Христа — основывается на Священном Писании и патристических свидетельствах, таких как Игнатий Антиохийский, Ориген, Василий Кесарийский, Ефрем Сирин и Ириней Лионский. Армянская богословская мысль, сформированная как переводами с греческого и сирийского, так и оригинальными трудами, полностью отражает преданность ортодоксальному мариологическому учению. Автор также анализирует еретические учения (например, эбиониты, карпократиане, антикокомариане), которые отвергали вечное девство Богородицы, противопоставляя их единогласному мнению отцов Церкви. В работе рассматриваются сложные экзегетические вопросы, касающиеся терминов «жена», «братья Иисуса» и «первенец», и объясняется их соответствие догмату о девстве. Особое внимание уделено также литургическим и иконографическим аспектам, подтверждающим почитание Пресвятой Девы в церковной традиции. Исследование представляет собой важный вклад в осмысление армянской мариологии в контексте Вселенской Церкви. This study explores the doctrinal foundation and theological development of the concept of the perpetual virginity of the Blessed Virgin Mary (Aeiparthenos) within early Christian and Armenian patristic literature. The article demonstrates how this Marian dogma—affirming that Mary remained a virgin before, during, and after the birth of Christ—was not only grounded in Scripture but also defended and elaborated by Church Fathers. Key references include the testimonies of Ignatius of Antioch, Origen, Basil of Caesarea, Ephrem the Syrian, and Irenaeus of Lyons. Armenian theological thought, enriched through translations from Greek and Syriac, as well as original compositions, reflects a deep commitment to the Orthodox Marian doctrine. The text further addresses early heresies (e.g., Ebionites, Carpocratians, Antidicomarianites), which rejected Mary’s perpetual virginity, and contrasts them with the orthodox patristic consensus. Particular attention is given to the exegetical treatment of scriptural passages concerning Mary’s title as “woman,” the “brothers of Jesus,” and the phrase “firstborn son,” showing how these were reconciled with the doctrine of perpetual virginity. Liturgical and iconographic evidence is also included to demonstrate the veneration of the Theotokos’ virginity in church tradition. This work significantly contributes to the understanding of Marian theology in the Armenian Church and its consonance with broader Christian orthodoxy.
Keywords: Կրօնագիտական